The development of small enterprises in Bulgaria, Czech Republic and the Russian Federation - Eckhard J. Dittrich; Heiko Schrader; Christo Stojanov (Journal for East European Management Studies, 2008)
During the past, the evaluation of the chances of economic transformation and development of Eastern Europe was largely shaped by the view on the modernization and organizational restructuring of large enterprises/combines. Various scholars were sceptical how far these could contribute to a functioning market economy, due to their heritage from the planned economy. The authors therefore investigated how far small entrepreneurs support the transformation process to a market economy. Quantitative and qualitative research was done in Bulgaria, Czech Republic and the Russian Federation in 2003 and 2004 to provide a comprehensive image about the milieu of small enterprises and their ways of operation. – – In der Vergangenheit wurden die Chancen ökonomischer Transformation und der Entwicklung Osteuropas von der Perspektive der Modernisierung und organisationale Umstrukturierung der Großunternehmen/Kombinate betrachtet. Es herrschte Skepsis, ob sie mit ihrem Erbe der Planwirtschaft zu einer funktionierenden Marktwirtschaft beitragen könnten. Deshalb untersuchten die Autoren, inwieweit Kleinunternehmer den Transformationsprozess zur Marktwirtschaft unterstützen. In den Jahren 2003 und 2004 führten die Autoren quantitative und qualitative Forschung in Bulgarien, Tschechien und der Russischen Föderation durch, um ein möglichst umfassendes Bild zu erhalten über das Milieu von Kleinunternehmen und ihre Art zu operieren.
Keywords: 650; transformation; small entrepreneurs; networks; Russia; Czech Republic; Bulgaria